Decentralized multi-agent reinforcement learning based on best-response policies - Gabler, Volker; Wollherr, Dirk (Frontiers in Robotics and AI, 2024)
Multi-agent systems are an interdisciplinary research field that describes the concept of multiple decisive individuals interacting with a usually partially observable environment. Given the recent advances in single-agent reinforcement learning, multi-agent reinforcement learning (MARL) has gained tremendous interest in recent years. Most research applies a fully centralized learning scheme to ease the transfer from the single-agent domain to multi-agent systems. In contrast, we claim that a decentralized learning scheme is preferable for applications in real-world scenarios as this allows to deploy a learning algorithm on an individual robot rather than deploying the algorithm to a complete fleet of robots. Therefore, this article outlines a novel actor-critic (AC)-approach tailored to cooperative MARL problems in sparsely rewarded domains. Our approach decouples the MARL problem into a set of distributed agents that model the other agents as responsive entities. In particular, we propose to use two separate critics per agent to distinguish between the joint task reward and agent-based costs as commonly applied within multi-robot planning. On the one hand, the agent-based critic intends to decrease agent-specific costs. On the other hand, each agent intends to optimize the joint team-reward based on the joint task critic. As this critic still depends on the joint action of all agents, we outline two suitable behavior models based on Stackelberg-games: a game against nature and a dyadic game against each agent. Following these behavior models, our algorithm allows full decentralized execution and training. We evaluate our presented method using the proposed behavior models within a sparsely rewarded simulated multi-agent environment. While our approach already outperforms the state- of-the-art learners, we close this article by outlining possible extensions of our algorithm that future research may build upon.